2005
DOI: 10.1200/jco.2005.06.154
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Comparing Iridium Implant Plus External-Beam Radiation Therapy With External-Beam Radiation Therapy Alone in Node-Negative Locally Advanced Cancer of the Prostate

Abstract: The combination of IM plus EBRT was superior to EBRT alone for BCF and postradiation biopsy. This trial provides evidence that higher doses of radiation delivered in a shorter duration result in better local as well as biochemical control in locally advanced prostrate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
184
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(201 citation statements)
references
References 20 publications
8
184
0
9
Order By: Relevance
“…Increasingly, conformal radiation delivery techniques have safely escalated the dose to the prostate by either increasing the number of daily fractions [1][2][3] or adding a boost [4][5][6][7]. These approaches increase the delivered bioequivalent dose (BED), and consequently the biochemical control rate, but are associated with additional treatment time or, in the case of a brachytherapy boost, an invasive procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, conformal radiation delivery techniques have safely escalated the dose to the prostate by either increasing the number of daily fractions [1][2][3] or adding a boost [4][5][6][7]. These approaches increase the delivered bioequivalent dose (BED), and consequently the biochemical control rate, but are associated with additional treatment time or, in the case of a brachytherapy boost, an invasive procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent prospective randomized trials have demonstrated that low RT doses (≤ 70 Gy) are inadequate for the curative treatment of clinically localized prostate cancer [34][35][36][37]. Moreover, higher doses (≥ 76 Gy) are associated with extended survival rate and reduced distant metastasis as well as improvement in both biochemical and clinical local control for prostate cancer [21,38].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Studies have shown a reduced risk of recurrence with the addition of brachytherapy to EBRT. [13][14][15] An analysis of a cohort of 12,745 highrisk patients found that treatment with brachytherapy (hazard ratio [HR], 0.66; 95% CI, 0.49-0.86) or brachytherapy plus EBRT (HR, 0.77; 95% CI, 0.66-0.90) lowered disease-specific mortality compared with EBRT alone. 16 The addition of ADT to brachytherapy and EBRT is common for patients at high recurrence risk.…”
Section: Pros-9mentioning
confidence: 99%